Potenziale städtischer Gewerbebrachflächen für eine integrierte Stadtentwicklung: Monitoring für ein nachhaltiges Flächenmanagement am Beispiel der wieder wachsenden Stadt Leipzig. Issue 2 (3rd April 2018) - Banzhaf, Ellen; Arndt, Thomas; Ladiges, Jan
Abstract: Urban brownfields have been an internationally recognised topic for many years and exist in industrialised countries worldwide. After decades of severe shrinkage, Leipzig, Germany, is now a fast-growing city. It serves as an excellent example to discuss the redevelopment of urban brownfields for an integrated urban development. We investigate the potentials of brownfields through land-use monitoring. In our field work, we mapped 783 brownfields in all of the city's commercial zones, including size, geographic position and spatial assignment, land surface characteristics and surrounding infrastructure. Spatial distribution of brownfields in the planning districts as well as land-use pat- terns was of great concern regarding vegetation succession stages and sealed surfaces. Infrared aerial colour photos supported our field information, gathered in a GIS-based information tool of urban districts for the planning division. More than 80% of all derelict land is less than one hectare in size and thus a major challenge in terms of individual recycling. Private ownership hampers redevelopment. Due to advanced succession stages there is a high potential for renaturalisation into coherent green spaces. Pressures on land use demand the readjustment of green infrastructure development in an urban planning masterplan. The project is based on scientific collaboration with the City of Leipzig's Authority of Urban Planning, Germany. English title: Potential Performance of Commercial Urban Brownfield Sites in Integrated Urban Development – Monitoring for Sustain- able Land-Use Management Based on the Ex- ample of the City of Leipzig